GERIATRIC NURSING CARE MANAGEMENT FOR Mr. E WITH HYPERTENSION AT THE ELDERLY SOCIAL SERVICE UNIT (UPTD) BINJAI CITY, NORTH SUMATRA PROVINCE - Ade kristi; Herna Rinayanti Manurung; Tahan Hasibuan; Kevin Batubara; Buya Fadhil; Stevani Ezra Poibe; Selvia Souraya Lubis (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Hypertension is a chronic condition that cannot be cured but can be managed. The incidence of hypertension among older adults is increasing globally, including in Indonesia, due to aging processes and degeneration (Iqbal & Handayani, 2022). The general objective of this study is to implement nursing care management for patients with hypertension at the Social Elderly Care Unit (UPTD Pelayanan Lanjut Sosial) in Binjai City, North Sumatra Province, in 2025. The World Health Organization (WHO) estimates that the global prevalence of hypertension currently reaches 22% of the total world population. The African continent has the highest prevalence, at 27%, while the Southeast Asia region ranks third with a prevalence of 25% of the total population. Data from the Indonesian Ministry of Health in 2018 show that the prevalence of hypertension among the elderly is quite high, with details as follows: the age group 65–74 years is 55.2%, and those over 75 years old is 69.5% (Kusumo, 2021). The results of this study indicate that 34 out of 198 elderly individuals suffer from hypertension, showing a prevalence rate of 22%. The 2023 Indonesian Health Survey (SKI) showed a decline in hypertension prevalence among those aged 18 years and older, with a prevalence rate of 30.8%. Based on the data obtained, the number of hypertension cases recorded in 2023 was 2,333 cases. In North Sumatra Province, the prevalence of hypertension reached 6.7% of the total population. This means that approximately 12.42 million people suffer from hypertension, spread across various districts in the province.